To what extent are foreign language anxiety and foreign language enjoyment related to L2 fluency? An investigation of task-specific emotions and breakdown and speed fluency in an oral task - Bielak, Jakub (Language teaching research : LTR, 2025)
The relationship between foreign language anxiety (FLA) and foreign language enjoyment (FLE) experienced during a creative collaborative oral English-as-a-foreign-language task, and the relationships between FLE/FLA and task speech fluency were investigated. The task was performed by mid-intermediate/high-intermediate English learners (N = 43) in groups and culminated in 2-minute monologues by every participant, the breakdown (the ratio and length of mid- and end-AS unit pauses) and speed (mean length of run, articulation rate, and phonation time ratio) utterance fluency of which was measured. The relationship between FLA and FLE fluctuated between task parts, form negligible to medium-strong negative. There were numerous negative links between FLA and fluency, and less numerous positive links between FLE and fluency of various strength. These lend support to earlier claims that FLA is associated with impaired second language (L2) outcomes and positive emotions may facilitate L2 learning/performance. The links between fluency and FLA and FLE experienced during collaborative L2 processing/practice preceding the monologue the fluency of which was examined were more frequent and stronger than links with the emotions during the monologue, pointing to the possible depletion and improvement of L2 processing caused respectively by FLA and FLE especially during this stage. The emotions were linked especially with fluency indices associated with speech formulation/encoding. In regression analyses, proficiency was the strongest predictor of fluency, followed by much weaker predictive power FLA and then FLE, which may be related to participants’ relatively high L2 advancement. The results imply that L2 teachers exploit the emotional impact of learning tasks and attend to the emotional atmosphere of L2 classes, especially their enjoyability.